Effects of dietary protein levels on the growth of Luciobarbus xanthopterus juveniles (Heckel, 1843) - Jabir, A.A. (Mesopotamian Journal of Marine Sciences, 2021)
The aim of the present study is to investigate the effect of four fish dietary protein levels (30%, 35%, 40% and 45%) on the growth of Luciobarbus xanthopterus juveniles. About 240 fish of average weight of 18.4 g were kept in eight small letter tanks for 8 weeks at the Marine Science Center aquaculture room. Two replicates for each treatment with 30 fish for each replicate were used. A number of growth parameters were estimated during the experiment. The environmental factors measured were; water temperature, DO, salinity and pH. The highest average weight gained was 21.14 g ± 0.33 with the 40% dietary protein level, while the lowest average weight was 19.68 g ± 0.50. The highest weight gained was recorded at 40% dietary protein level. The highest weight gain and weight increase were significantly different (p<0.05) at 40% dietary protein level. Their values were 21.14 g ± 0.33 and 2.11 ± 0.06, respectively. The lowest weight gain and weight increase were at 45% protein level, with values of 19.68 g ± 0.50 and 1.09 ± 0.05, respectively. The weight increase was 2.11 ± 0.06. Significant differences (p<0.05) have been noticed in this protein level, however, the other dietary levels showed no significant increase. The highest rate of daily weight increase were recorded at the 30%, 35% and 40% levels and the significant differences (p<0.05) among these levels were in apparent. However, the weight increase rate of 2.12 was dropped at 45% level to 1.41 ± 0.033. The highest rate of specific growth was recorded at the 35% protein level with value of 0.31 g/day with no significant differences (p<0.05) between the various levels. Finally, it could be concluded from this study that the lowest specific growth 5.64% was recorded at the 45% protein level and the highest relative growth 11.06% was recorded at the dietary protein level of 35%.